1990
DOI: 10.1007/bf01104142
|View full text |Cite
|
Sign up to set email alerts
|

Seed protein yield from someCrotalaria spp andin vitro nutritional quality of that fromC. juncea

Abstract: Seed Protein Concentrates (SPC) of 6 species of Crotalaria were extracted and the extractabilities of SPC, total N and protein N determined. SPC of high yielding species (C. Juncea) was analyzed for the contents of amino acids, ash, phosphorus, sugar, starch, fibre and calories, as well as for in vitro digestibility. Results indicate the promising potential of C. juncea for SPC yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…They are used as a source of fibers, silage, and green manure for nitrogen fix-ation (Dempsey 1975;Ramos et al 2001); as cover crops for control of weeds, nematodes, and soil erosion; and as ornamentals (Miller 1967). Some Crotalaria species can be used as forage for horses and cattle owing to the large amounts of water-soluble gums and proteins in their seeds (Purseglove 1981;Pandey and Srivastava 1990). Despite this commercial value, the genetic diversity of Crotalaria species germplasm has not been assessed.…”
Section: Introductionmentioning
confidence: 99%
“…They are used as a source of fibers, silage, and green manure for nitrogen fix-ation (Dempsey 1975;Ramos et al 2001); as cover crops for control of weeds, nematodes, and soil erosion; and as ornamentals (Miller 1967). Some Crotalaria species can be used as forage for horses and cattle owing to the large amounts of water-soluble gums and proteins in their seeds (Purseglove 1981;Pandey and Srivastava 1990). Despite this commercial value, the genetic diversity of Crotalaria species germplasm has not been assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Because of inadequate supplies and shortage of food proteins, there has been a constant search of unconventional legumes as new protein sources for use as both functional food ingredients and nutritional supplements (Tjahjadi et al, 1988;Pandey and Sirvastava, 1990;Morrow, 1991;Onweluzo et al, 1994). Onweluzo et al (1994) have reported the potential application of some lesser known legume seed fractions from the developing countries as functional food ingredients.…”
Section: Introductionmentioning
confidence: 99%
“…Species of this genus are wide spread throughout tropical, subtropical and to lesser extent temperate countries. It is used as forage for cattle owing to the large amounts of water soluble gums and proteins in their seeds (Pandey and Srivastava 1990). Although there are few reports of regeneration in vitro earlier, (Ohara et al 2000) the viability of transgenics of this plant has not been exploited as it is a legume.…”
Section: Introductionmentioning
confidence: 99%